1991
DOI: 10.1200/jco.1991.9.12.2104
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective assessment of recombinant leukocyte A human interferon with or without aspirin in advanced renal adenocarcinoma.

Abstract: We performed a prospective, controlled trial of recombinant leukocyte A interferon (IFN-alpha 2A) with or without aspirin (ASA) in 176 patients with assessable advanced renal cell cancer in light of a 34% response rate (10 of 29 patients) from the two-agent regimen in an earlier nonrandomized trial. This encouraging result was substantially higher than the 15% response rate typically achieved with IFN therapy alone. Eighty-seven patients received IFN-alpha 2A 20 x 10(6) U/m2 intramuscularly three times a week,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…20,26 Adjuvant studies Aspirin is an unlikely anticancer drug, and its emergence as an important potential adjuvant agent prompts us to reflect about how we select and design anticancer therapies for development. Aspirin has no demonstrable activity in patients with overt metastatic cancer, 53,54 and it probably would never have been detected as a potential anticancer agent by using the standard NCI-60 cancer cell line drug screening assay (a cell-based assay developed by the NCI, that evaluates drug compounds by their ability to inhibit human tumour cell growth in culture). 55 Aspirin has a lower affinity and specificity for the COX-2 isoenzyme than COX-2-selective inhibitors (such as, celecoxib), and is only weakly anti-inflammatory at standard doses.…”
Section: Primary Preventionmentioning
confidence: 99%
“…20,26 Adjuvant studies Aspirin is an unlikely anticancer drug, and its emergence as an important potential adjuvant agent prompts us to reflect about how we select and design anticancer therapies for development. Aspirin has no demonstrable activity in patients with overt metastatic cancer, 53,54 and it probably would never have been detected as a potential anticancer agent by using the standard NCI-60 cancer cell line drug screening assay (a cell-based assay developed by the NCI, that evaluates drug compounds by their ability to inhibit human tumour cell growth in culture). 55 Aspirin has a lower affinity and specificity for the COX-2 isoenzyme than COX-2-selective inhibitors (such as, celecoxib), and is only weakly anti-inflammatory at standard doses.…”
Section: Primary Preventionmentioning
confidence: 99%
“…There was no evidence that survival was different (HR 1.01, 95% CI: 0.81–1.27, P =0.09) and aspirin appeared to be well tolerated. Another trial found no evidence of a survival benefit (HR 0.91, 95% CI: 0.63–1.31, P =0.60) when 176 patients with advanced renal cell cancer received interferon- α with or without aspirin 2400 mg daily (Creagan et al , 1991). A small trial of only 66 patients evaluated 1200 mg of aspirin daily compared with placebo as adjuvant treatment for Duke's B2 and C colorectal cancer (HR for survival 0.65, 95% CI: 0.02–18.06, P =0.90) (Lipton et al , 1982).…”
Section: Aspirin As An Anti-cancer Agent: Clinical Evidencementioning
confidence: 99%
“…In phase II studies these drugs are associated both as single agent and in combination, with a response rate between 6 and 25% and a median survival of 8-14 months (Umeda and Niijima, 1986;Creagan et al, 1991;Gore et al, 1994;Fyfe et al, 1996). In a randomized phase III study the response rates of patients treated with IL-2, IFN-α or the combination were 6.5%, 7.5% and 18.6% respectively.…”
Section: Discussionmentioning
confidence: 99%